Pelatihan Dasar Penyusunan Laporan Keuangan Koperasi Perhutani di Saradan - Dita Mariska Candra Darusman; Diyah Santi Hariyani (Universitas Merdeka Madiun, 2024)
Lack of understanding of cooperative accounting, namely Financial Reports, is a problem that needs to be faced by forestry cooperatives, this problem is the background for the training activities carried out. The aim of this activity is to increase understanding and knowledge about cooperative financial reports for cooperative administrators and employees both conceptually and technically. The location of the activity is at the Perhutani Saradan Cooperative. The method used in this training activity is lecture and discussion. Carrying out this training activity provides benefits in increasing understanding and knowledge of financial reports conceptually and technically and can then be carried out to support business activities in cooperatives. The results of the evaluation of training activities show that the level of understanding of the material presented is very good. Considering the great benefits provided by training activities, the same training can be carried out in organizations or community groups such as MSMEs so that it can contribute to increasing their knowledge in managing finances more effectively and efficiently.